LEAN MANUFACTURING: case study on the use of Lean concepts to optimize an assembly line - Morais, Adrisio Lucas de; Ramalho Reis Filho, Ramilio (Revista Interface Tecnológica, 2020)
This article deals with the implementation of the concepts of the Lean Manufacturing philosophy in a company that manufactures agricultural implements that has undergone great changes from the cost of the product to the production capacity, optimizing its production efficiency. The objective was to identify the main waste through flow mapping and apply the possible improvements, since currently a company to remain competitive needs to eliminate or reduce as much as possible all waste that does not generate value for the customer. In this work, the initial objective is to show how much lean tools can bring returns for companies. During the course, the impacts that the implementation could have on the entire company were analyzed, respecting the rules already implemented in other sectors. After all the work was done, it was possible to make measurements based on the before and after considering the new sector to show the project’s effectiveness.